REVIEW COMMUNITY COMPLIANCE AND AWARENESS IN USE OF SOCIAL MEDIA FROM PERSPECTIVE SOCIOLOGY OF LAW - Teguh Ferdiansyah Chusnein; Catharina Dewi Wulansari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Social media has become part important in life modern society , but also gives rise to challenge law new , like pollution Name good , speech hatred , and the spread of information lie . This research aim analyze level awareness and compliance law public in use of social media in Indonesia and role law as tool controller social . The approach used is juridical-sociological , which studies law No only as rule written but also as phenomenon social . Research results show that even though Law Number 11 of 2008 concerning Information and Transactions Electronics ( last changed with Law Number 1 of 2024) provides guidelines law , violation Still often happen consequence low literacy law , lack of digital education , and the lack of internalization mark ethics . From the perspective sociology law , compliance law depends on understanding and application norm social in digital interactions . This research emphasize importance education laws and approaches restorative For increase awareness law , so that social media can used in a way responsible responsible and harmonious in Indonesian society .